International Electron Devices Meeting. IEDM Technical Digest
DOI: 10.1109/iedm.1997.650425
|View full text |Cite
|
Sign up to set email alerts
|

Boron-enhanced-diffusion of boron: The limiting factor for ultra-shallow junctions

Abstract: Reducing implant energy is an effective way to eliminate transient enhanced diffusion (TED) due to excess interstitials from the implant. It is shown that TED from a fixed Si dose implanted at energies from 0.5 to 20 keV into boron dopingsuperlattices decreases linearly with decreasing Si ion range, virtually disappearing at sub-keV energies. However, for subkeV B implants diffusion remains enhanced and xj is limited to 2100 nm at 105OOC. We term this enhancement, which arises in the presence of B atomic conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 2 publications
1
20
1
1
Order By: Relevance
“…Nevertheless, different interpretations and some controversies appeared in the literature. [1][2][3] In this letter we give a further contribution regarding the diffusion of B implanted with energies lower than 1 keV.…”
Section: ͓S0003-6951͑99͒02939-3͔mentioning
confidence: 99%
“…Nevertheless, different interpretations and some controversies appeared in the literature. [1][2][3] In this letter we give a further contribution regarding the diffusion of B implanted with energies lower than 1 keV.…”
Section: ͓S0003-6951͑99͒02939-3͔mentioning
confidence: 99%
“…A recent study by Agarwal et al has found evidence of the formation of solid phase SiB 4 once boron concentrations have exceeded ϳ6%. 26 However, in this study the peak concentration for the substrate subjected to the highest BF 2 dose did not exceed ϳ0.6%; therefore SiB 4 formation would not be anticipated. Boron precipitation or clustering, 27,28 however, may have formed since the solid solubility of boron in silicon at 950ЊC is reported to be only ϳ1 ϫ 10 20 cm Ϫ3 .…”
Section: Resultsmentioning
confidence: 82%
“…In contrast to the reduction in enhancement to 1x obser~cd for ULE Si-, a saturation in the reduction of diffusivity enhancement at 4x is seen for the B. implants at 1 and 0.5 keV (Fig. 7) [18]). …”
Section: Ts(t)= Tf+(ti -Tf)exp[-(t/t)p]mentioning
confidence: 76%